Proses Pembelajaran Bahasa Indonesia di Masa Pandemi Covid-19 - Sri Idawati (Universitas Indraprasta PGRI, 2022)
Abstract: This study aims to gain an in-depth understanding of the curriculum, objectives, materials, strategies, approaches, media, and evaluation of Indonesian language learning at SMPN 265 Jakarta. This study uses a qualitative approach with phenomenological methods. Data were collected through observation, interviews, and documentation. Data analysis used the Creswell model, namely: organizing, reading, describing, classifying, interpreting, and narrating the data. The results of the study show: (1) Learning uses the 2013 national curriculum which is adapted to the covid-19 situation; (2) learning objectives are focused on achieving two aspects of core competence, namely KI-3 (knowledge) and KI-4 (skills) in Indonesian; (3) The material used is text-based, namely sourced from mandatory textbooks issued by the government; (4) Using application-based learning media in online networks (google site, google form, google zoom/meet, whatsapp, youtube, email, instagram, facebook, and telephone); (5) the evaluation is conducted online which includes three domains, namely knowledge, skills and attitudes. The evaluation was carried out 20 times which was divided into two aspects, namely process evaluation 18 times (every meeting) and evaluation of results 2 times (UTS and UAS).Keywords: Keywords: Learning, Indonesian, Phenomenology.